2017
DOI: 10.1039/c7tc01261f
|View full text |Cite
|
Sign up to set email alerts
|

Thiophene-S,S-dioxidized diarylethenes for light-starting irreversible thermosensors that can detect a rise in heat at low temperature

Abstract: Thiophene-S,S-dioxidized diarylethenes having a trialkylsilyl group at the reactive positions underwent photoinduced coloration and thermal bleaching even at −40 to −30 °C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“… [5] Our previous contribution to the field revealed that arene‐Ru II complexes of type II (7‐membered chelate ring involving coordination of nitrogen atoms from both pyridines) could be accessed from Z ‐2,2’‐azobispyridine, albeit with a stability in solution not exceeding several hours, and underwent clean and complete irreversible Z→E isomerization with concomitant rearrangement of the coordination pattern in response to light or redox stimuli (Scheme 1). [5] The growing interest in irreversible photochromic systems for applications such as secret display materials, [6] light‐activated thermosensors [7] and chemical probes, [8] or photo‐initiation of catalytic transformations [9,10] prompted us to seek for new type II complexes with increased thermal stability in the dark [11]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… [5] Our previous contribution to the field revealed that arene‐Ru II complexes of type II (7‐membered chelate ring involving coordination of nitrogen atoms from both pyridines) could be accessed from Z ‐2,2’‐azobispyridine, albeit with a stability in solution not exceeding several hours, and underwent clean and complete irreversible Z→E isomerization with concomitant rearrangement of the coordination pattern in response to light or redox stimuli (Scheme 1). [5] The growing interest in irreversible photochromic systems for applications such as secret display materials, [6] light‐activated thermosensors [7] and chemical probes, [8] or photo‐initiation of catalytic transformations [9,10] prompted us to seek for new type II complexes with increased thermal stability in the dark [11]…”
Section: Introductionmentioning
confidence: 99%
“…[5] Our previous contribution to the field revealed that arene-Ru II complexes of type II (7-membered chelate ring involving coordination of nitrogen atoms from both pyridines) could be accessed from Z-2,2'-azobispyridine, albeit with a stability in solution not exceeding several hours, and underwent clean and complete irreversible Z!E isomerization with con-comitant rearrangement of the coordination pattern in response to light or redox stimuli (Scheme 1). [5] The growing interest in irreversible photochromic systems for applications such as secret display materials, [6] light-activated thermosensors [7] and chemical probes, [8] or photo-initiation of catalytic transformations [9,10] prompted us to seek for new type II complexes with increased thermal stability in the dark. [11] Considering that the introduction of strong electron donating groups in position 4 of the pyridine ring would increase the NÀ Ru binding strength, [12] we report herein an efficient synthetic route to two novel 2,2'-azobis-4,4'-N-dialkylaminopyridine ligands 2 and 3 (Scheme 2), the study of their photochromic behavior and their coordination ability to Ru II centers.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, the 6π electrocyclic reaction between hexatriene and cyclohexadiene skeletons is one of the typical pericyclic reactions. The Woodward–Hoffmann (WH) rule and the van der Lugt/Oosterhoff model in the 1960s established the basis for the mechanism of the 6π electrocyclic reaction, ,, but it still fascinates many researchers in the research fields of advanced optical measurements and theoretical calculations because the 6π electrocyclic reaction proceeds on a femtosecond scale and goes through complex electronic states including two-electron excited configurations. , Moreover, in terms of applications, the 6π electrocyclic reaction is also responsible for the driving process of photoswitching of diarylethene that is one of the representative photochromic molecules and has various potential applications in research fields of material and life sciences. Therefore, gaining insight into the dynamics of the 6π electrocyclic reaction is very important from both fundamental and application perspectives.…”
mentioning
confidence: 99%
“…8,9 Moreover, in terms of applications, the 6 electrocyclic reaction is also responsible for the driving process of photoswitching of diarylethene that is one of the representative photochromic molecules and has various potential applications in research fields of material and life sciences. [10][11][12][13][14][15][16][17] Therefore, gaining insight into the dynamics of the 6 electrocyclic reaction is very important from both fundamental and application perspectives. Figure 1a shows the thermal ring-opening reaction (cycloreversion) of diarylethene derivatives undergoing 6 electrocyclic reaction between hexatriene and cyclohexadiene skeltons.…”
mentioning
confidence: 99%